(untitled) (Faridpur Medical College Journal, 2017)
Distal radial fractures are most common fractures accounts 15% of whole skeletal injuries, as high as 40% to 49% are considered to be unstable that requires surgical fixation. The purpose of the study was to ascertain good functional hand by using volar locking plate & screws, as with locking system, distal screws are locked to the plate, which stabilized the screws against lateral movement (toggle effect), thus providing a "single bone-plate-screws construct" which producing a scaffold in the mostly cancellous distal radial metaphysis, so preventing from collapse. This study was done from January 2007 to December 2008 at National Institute of Traumatology & Orthopaedic Rehabilitation (NITOR). Total numbers of cases were 17. All patients were admitted in hospital & most of them returned home within 4 days. Most patients were managed early within 1-10 days of injury. Most patients were Fernandez type 1, type 2, and type 3. Most patients were in the age group of 4th decade. All patients were followed up for a period of at least 3 months, mean follow up period was 6 months. Results showed that wrist pain, wrist stiffness, reduced grip strength were minimum with volar locking plate & screws as there is minimal radial shortening, radial angulation, volar tilt & ulnar variance and wrist flexion, wrist extension, ulnar deviation, supination, pronation were very good. So, the trauma surgeons can safely use this procedure. Faridpur Med. Coll. J. Jul 2016;11(2): 62-66